The anticancer effect of local vernonia amygdalina in combination with standard chemotherapy drug, tamoxifen on breast cancer cell line, MCF-7 - Jian, Chin Tze (2018)
Vernonia amygdalina (VA) is a broadly used local plant in Africa for both nutritional and therapeutic purposes. Nevertheless, different geographical origins, locality, climate conditions and time of harvesting could influence the biological activities of the plant. Albeit of the advancement in medical field, the prevalence of breast cancer still increases globally and many data have shown that among all the different types of cancers, it is one of the cancers that contribute to the majority of the mortality. Moreover, the risk and detrimental side effects of chemotherapy are fast compensating its benefits. Therefore, this study focused on combination treatment of local VA and tamoxifen towards breast cancer cell line, MCF7 in an effort to reduce the nonselective effect on normal cells, NIH 3T3. The cytotoxicity activities of VA alone and combination with tamoxifen towards MCF7 and NIH 3T3 cell lines were examined using MTT assay. The IC50 values on MCF7 for VA (1.10 ± 1.78 mg/ml), tamoxifen (0.06 ± 0.04 mg/ml) and combination (0.09 ± 0.10 mg/ml) were obtained. VA was also found to be non-deleterious towards normal cells and had the IC50 values of NIH 3T3 raised in combination treatment (tamoxifen alone: 0.28 ± 0.22 mg/ml, combination: 3.69 ± 2.74 mg/ml). Antagonistic combination (CI>1) was also discovered between VA and tamoxifen. The combination treatment managed to have an anti-proliferative effect on MCF7 cells and reduced toxicity on normal cells.Nuclear staining by Hoechst 33258 suggested the occurrence of apoptosis based on the presence of bright fluorescence in the cells treated with combination treatment. In conclusion, VA exhibited potential selective anticancer properties in MCF7 cells by possibly inducing apoptotic cell death and it has a promising opportunity to be used clinically at the future.